The Role of Public Relations in Promoting Islamic Tourism - Harjoni, Harjoni; Tan, Marcus; Linm, Sofia (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Islamic tourism has emerged as a rapidly growing sector within the global travel industry, driven by increasing demand for Shariah-compliant services and culturally sensitive travel experiences. Effective public relations (PR) strategies play a crucial role in promoting Islamic tourism by shaping perceptions, enhancing destination branding, and facilitating engagement with Muslim travelers. The integration of PR efforts into Islamic tourism marketing ensures that destinations effectively communicate their adherence to Islamic values while maintaining global appeal. Understanding how PR contributes to the development and promotion of Islamic tourism is essential for creating sustainable and competitive tourism strategies. This study aims to analyze the role of PR in positioning Islamic tourism destinations and fostering positive stakeholder engagement. A qualitative research design is employed, incorporating content analysis of tourism campaigns, interviews with PR professionals, and case studies of successful Islamic tourism destinations. Findings reveal that strategic media engagement, digital PR campaigns, and community-driven storytelling significantly influence the visibility and attractiveness of Islamic tourism destinations. Social media platforms and influencer collaborations emerge as effective tools for shaping travel narratives and enhancing tourist engagement. The study concludes that public relations efforts must integrate Islamic cultural elements with modern communication techniques to successfully promote Islamic tourism.